2022
DOI: 10.3390/jintelligence10030052
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes and Reorganization of Creativity and Intelligence Indices in Schoolchildren and University Students

Abstract: Despite the lasting interest towards the relationship between intelligence and creativity, comparably less attention is paid to its age-related changes. Our paper considers the organization of fluid intelligence and psychometric indicators of creativity and is based on the experimental data obtained for children aged 11 (n = 99) and for young adults (n = 77). We used two figural and verbal tasks with and without time limit. We found that the age-related differences in creativity are dependent on the context an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Lately, Beghetto proposed the existence of an ideational‐code switching theory, according to which young children tend to move from ideas that are personally unique and meaningful to the production of ideas that are interpersonally original and appropriate as they are more able to take into account more complex sociocultural cues (Beghetto, 2007; Beghetto & Kaufman, 2007). In general, however, a large body of research has demonstrated that creative thinking also follows complex developmental paths and tends to unfold in line with the improvement of abstract thinking and reasoning during childhood and adolescence and through early adulthood (Razumnikova & Bakaev, 2022; Russ & Fiorelli, 2010; Urban, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Beghetto proposed the existence of an ideational‐code switching theory, according to which young children tend to move from ideas that are personally unique and meaningful to the production of ideas that are interpersonally original and appropriate as they are more able to take into account more complex sociocultural cues (Beghetto, 2007; Beghetto & Kaufman, 2007). In general, however, a large body of research has demonstrated that creative thinking also follows complex developmental paths and tends to unfold in line with the improvement of abstract thinking and reasoning during childhood and adolescence and through early adulthood (Razumnikova & Bakaev, 2022; Russ & Fiorelli, 2010; Urban, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned approaches need to be further considered with age-related variables ( Sternberg, 1985 ; Razumnikova and Bakaev, 2022 ). This is because diverse cultural and contextual factors change constantly and influence individuals in distinct ways.…”
Section: Introductionmentioning
confidence: 99%